Testing hypotheses of habitat use and temporal activity in relation to body plan in a Mediterranean lizard community - Rugiero, L.; Capula, M.; Dendi, D.; Petrozzi, F.; Fa, J.E.; Funk, S.M.; Burke, R.L.; Luiselli, L. (Canadian Science Publishing, 2021)
A body plan (= bauplan) is a suite of morphological characters shared by phylogenetically related animals at some point during their development. Despite its value, the bauplan concept is still rarely employed to characterize functional groups in community ecology. Here, we examine habitat use and spatio-temporal activity correlates of an entire seven-species community of lizards with different bauplans. The study was carried out in three locations in central Italy, encompassing a complex landscape with a patchy mosaic of a wide variety of habitats and microclimates. We tested four hypotheses regarding niche breadth, habitat use and activity patterns. The first hypothesis, niche complementarity, in which species with similar body shapes should non-randomly partition available habitats, was not supported. By contrast, the hypotheses that larger-bodied species should have a wider niche breadth, that slower species should inhabit habitat types of higher cover, and species inhabiting open sunny habitats should exhibit more seasonally variable activity patterns, were all supported by the data. Sympatric lizard communities in our study area were clearly organized by autecological constraints and eco-physiological attributes.